FORM OF THE UKRAINIAN STATEHOOD: BETWEEN UNITARISM AND FEDERALISM - Sergej Sergeevich Zhiltsov (Проблемы постсоветского пространства, 2017)
This paper studies the state government of Ukraine. It analyzes the key factors which have been shaping the outlook of the Ukrainian elite for over two decades of the state development. The events going on in the southeastern areas in 2014-2015 and the approaches of the present Ukrainian powers to addressing this issue are studied.